1996
DOI: 10.1089/cap.1996.6.119
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Changes in Symptoms and Neurotransmitter Indices during Maintenance Treatment with Clozapine or Conventional Neuroleptics in Adolescents and Young Adults with Schizophrenia

Abstract: A study of 40 young patients (age 14-22 years) with DSM-III-R schizophrenia (without substance abuse) was conducted following a mean of 3.4 years of neuroleptic treatment. After failing on conventional agents in clinical trials lasting a mean of 2 years, 20 patients were prospectively maintained on open-label clozapine (mean 324 mg daily), and another 20 patients continued on typical neuroleptics (mean 465 mg chlorpromazine-equivalents daily). Patients were then sampled for biochemical measures and assessed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 40 publications
3
34
0
Order By: Relevance
“…In agreement with our previous report including 40 adolescent patients with a one-year follow-up (Schulz et al, 1996), this six-week study confirmed that over the course of treatment the serum levels of serotonin increased during clozapine medication as compared to pretreatment levels. B anki (1978) first described elevated total blood serotonin concentrations due to clozapine treatment in adults.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with our previous report including 40 adolescent patients with a one-year follow-up (Schulz et al, 1996), this six-week study confirmed that over the course of treatment the serum levels of serotonin increased during clozapine medication as compared to pretreatment levels. B anki (1978) first described elevated total blood serotonin concentrations due to clozapine treatment in adults.…”
Section: Discussionsupporting
confidence: 93%
“…The finding of markedly increased plasma norepinephrine levels is in agreement with our results on long-term clozapine treatment (Schulz et al, 1996) and concurs with studies in adult patients, which report clozapine-induced increases in plasma and/or CSF levels of norepinephrine in adults with schizophrenia (Breier et al, 1994;Green et al, 1993;Lieberman et al, 1991;Pickar et al, 1992). Breier et al (1994) reported that clozapine produced a significant increase in plasma norepinephrine levels and that this increase was positively correlated with a reduction in symptoms as assessed with BPRS total scores and positive symptom scores.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Responders showed increased plasma MHPG and epinephrine during clozapine treatment compared to pretreatment with typical antipsychotics, whereas nonresponders did not. Plasma NE and 5-HT increased following clozapine treatment, but did not differentiate responders and nonresponders Schulz et al 1996 40…”
Section: Cognitive/neuropsychologicalmentioning
confidence: 94%
“…This search has resulted in the introduction of four "newer atypical APDs" (i.e., risperidone, olanzapine, quetiapine, and ziprasidone), all of which have important effects on both dopaminergic and serotonergic neurotransmitter systems. Because none of these compounds has been proven as efficacious as the prototype, clozapine, in the treatment of resistant cases, continued research is focusing on other neurotransmitter systems affected by clozapine.Clozapine profoundly increases norepinephrine (NE) levels in both CSF (Ackenheil 1989;Lieberman et al 1989;Lieberman et al 1991;Pickar et al 1992) and plasma (Pickar et al 1992;Green et al 1993;Davidson et al 1993;Breier 1994;Breier et al 1994b;Schulz et al 1996;Schulz et al 1997;Brown et al 1997;Fleischhaker et al 1998;Elman et al 1999), an effect not seen with typical APDs. In some (Breier et al 1994b;Schulz et al 1997;Fleischhaker et al 1998), but not all (Brown et al 1997) studies, plasma NE increases have been related to clinical improvement, suggesting that this pharmacological effect may play a role in clozapine's beneficial central actions.…”
mentioning
confidence: 99%